How Laws Regulate Migrant Sex Workers in Canada: To Protect or to Harm? - Lam, Yee Ling Elene (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2023)
Migrant sex workers in Canada are regulated and affected by a web of laws and policies at the federal, provincial, and municipal levels. This article lays out how these laws and policies, which claim to protect migrant workers, govern and harm their lives. Focusing on the experiences of migrants of Asian descent, this article explores how ill-conceived anti-trafficking laws and enforcement, including sex work-related criminal law, immigration laws that target and prohibit sex work, provincial human trafficking laws, and municipal laws regulating body rub services, conflate sex work with trafficking and further endanger migrant sex workers.